CONVERSATIONAL TABOO WORDS IN VIDEO GRAMMAR SUROBOYO - PRASETYA, SEPTIAN BUDI (Jurnal Ilmiah Mahasiswa FIB, 2013)
This research is a sociolinguistics study focusing on analyzing the conversation of Suro and Boyo in the "Video Grammar Suroboyo", by usinWardhaugh’s theory. Taboo is related to the culture meanings, which are expressed inlanguage. It means that language is used to avoid saying certain thing which is considered immoral and improper to the certain thing. The writer condected a studto analyze the taboo words used by Suro and Boyo in the Video Grammar SuroboyoThis study attempts to answer the following research questions: (1) What are the taboo words used in "Video Grammar Suroboyo? (2) What are the types of taboowords uttered by characters in "Video Grammar Suroboyo"?This study is a descriptive qualitative research as it is concerned with thetaboo words used by Suro and Boyo in "Video Grammar Suroboyo". In order toobtain the valid data, the researcher collected the data by downloading the "VideGrammar Suroboyo". Then the researcher listened and watched the video "VideGrammar Suroboyo" carefully to make it clear and valid data before being analyzed.Last, the researcher took a note of the taboo words expressed by the characters in thvideo.The result of the study showed that the taboo words found in the video arejancok (cok), asu, gatel (guatel), gaplek (guaplek), matane, raimu, matek, siletmu,and then were classified into taboo sex/copulative term (75%), bodilfunction (10,7%), excretion (7,1%), certain game/animal (2,4%), death (2,4%) andthe left hand (2,4%).Finally, the researcher suggests future researchers who analyze the similatopic to develop a study by analyzing taboo expressions from another point of viewbecause there are still many categories that have not been analyzed yet, such areligious matter and the left hand. Key words: Taboo, Taboo Words, Utterance, Sociolinguistics and Video Gramma Surabaya